Relationship between ionic radius and pressure dependence of ionic conductivity in water - Kumar, Parveen; Shukla, Ashok Kumar; Yashonath, Subramanian (Diffusion Fundamentals, 2007)
Experimental measurements of ionic conductivity in water are analysed in order to obtain insight into the pressure dependence of limiting ionic conductivity of individual ions (λ0) for ions of differing sizes. Conductivities of individual ions, λ0 do not exhibit the same trend as a function of pressure for all ions. Our analysis suggests that the effect of pressure on ionic conductivity depends on the temperature. At low temperatures, the effect of pressure on relatively small ions such as Li+ exhibit an increase in conductivity with pressure. Intermediate sized ions exhibit an increase in conductivity with increase in pressure initially and then at still higher pressures, a decrease in ionic conductivity is observed. Although there are data at low temperatures for ions of large radius, the effect of increased pressure is expected to lower conductivity with increase in pressure over the whole range. At higher temperatures, the dependence of conductivity on pressure changes and these changes are discussed. Divalent ions such as SO2−4 exhibit different trends as a function of pressure at different temperatures. Both the divalent ions (Ca2+ and SO2−4 ) for which experimental data exists, exhibit an increase with pressure at lower temperatures. At slightly higher temperatures, a maximum in conductivity is seen as a function of pressure over the same range of pressure.